Revision of Chloeia Savigny in Lamarck, 1818 from tropical American seas (Annelida, Amphinomidae) - Yáñez-Rivera, Beatriz; Salazar-Vallejo, Sergio I. (Zootaxa, 2022)
The species of Chloeia Savigny in Lamarck, 1818 include some of the most colorful amphinomid annelids in tropical seas. Their pigmentation patterns can be diagnostic but because some pigments may fade after ethanol preservation, they have been disregarded as useful taxonomic characters. In this contribution we revise the tropical American species of Chloeia, and we confirm stability of pigmentation patterns, the presence of cirriform branchiae along a few anterior chaetigers, and emphasize the size of eyes and of ventral cirri as diagnostic characters. Five species are redescribed and two ones are newly described; the redescribed species are C. entypa Chamberlin, 1919 from Western Mexico, C. euglochis Ehlers, 1887 from the Grand Caribbean (reinstated), C. pinnata Moore, 1911 from Southern California (extended southwards in Western Mexico), C. pseudeuglochis Augener, 1922 from Pacific Costa Rica (includes several records for a colorful shallow water species in the Eastern Pacific), and C. viridis Schmarda, 1861 from the Grand Caribbean, which is restricted to specimens having a single, dorsal longitudinal T-shaped band. New species are Chloeia nuriae sp. n. from the Gulf of California, and C. paulayi sp. n. from the Gulf of Mexico . Two other species previously recorded for the region, C. conspicua Horst, 1910 and C. flava (Pallas, 1766) are briefly characterized in order to avoid future misidentifications. Further, C. candida Kinberg, 1857 from the Virgin Islands, is regarded as indeterminable. A key to identify tropical American species of Chloeia is also included.